International Symposium onInformation Theory, 2004. ISIT 2004. Proceedings.
DOI: 10.1109/isit.2004.1365172
|View full text |Cite
|
Sign up to set email alerts
|

Security of quantum key distribution with imperfect devices

Abstract: We prove the security of the Bennett-Brassard (BB84) quantum key distribution protocol in the case where the source and detector are under the limited control of an adversary. Our proof applies when both the source and the detector have small basis-dependent flaws, as is typical in practical implementations of the protocol. We derive a general lower bound on the asymptotic key generation rate for weakly basis-dependent eavesdropping attacks, and also estimate the rate in some special cases: sources that emit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
851
0
2

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(858 citation statements)
references
References 37 publications
5
851
0
2
Order By: Relevance
“…f EC is the error correction efficiency and h(x) is the binary Shannon entropy [19,22]. For true single photon sources ∆ = 0 and the secret key rate is written as…”
Section: A Bb84 Without Decoy Statementioning
confidence: 99%
“…f EC is the error correction efficiency and h(x) is the binary Shannon entropy [19,22]. For true single photon sources ∆ = 0 and the secret key rate is written as…”
Section: A Bb84 Without Decoy Statementioning
confidence: 99%
“…Since Eve is unaware of Alice's basis choice, she will inevitably introduce errors in case of a basis mismatch between her basis and the one used by Alice and Bob. Eve will thus always be detected in a perfect implementation of a QKD system [5,6].…”
Section: Intercept-resend Attack Using Faked Statesmentioning
confidence: 99%
“…More generally, it has been shown that small deviations between the model and the implementation, such as imperfect preparation of the states by Alice or imperfect detection by Bob, can essentially be captured in the security model, at the expense of some extra privacy amplification [111]. Note that is not the case for attacks like blinding or Trojan horse, where the deviation from the security model is not small.…”
Section: Practical Security Of Qkd Implementations and Implementationmentioning
confidence: 99%